„Wojna kulturowa” w codzienności. Problem nauczania religii w szkole w dyskursie prawicowych portali informacyjnych (Przegląd Religioznawczy – The Religious Studies Review, 2020)
This article addresses the issue of cultural conflict (“cultural war”) that appears in contemporary media discourse around teaching religion in the public education system. The research is exploratory in nature, its purpose is to reconstruct and interpret the main conflict areas presented in the media discourse. The research included the discourse analysis of 3 intentionally chosen websites identified as right-wing or conservative both by journalists and media researchers in Poland. The author assumed that users and journalists working for right-wing portals treat religion as a natural element of their world-view and are interested in religious themes, which is why they pay more attention to it than journalists and recipients or publishers of left-wing media. The aim of the study was to find the basic topos that organize statements concerning religion at school. The results of the research showed that the metaphor of “cultural war” seems apt in relation to the Polish symbolic elites, because both statements and actions of politicians are antagonistic. The discourse on religion at school describes little about the importance of religion in the life of the individual and society, but reveals the separation between symbolic elites and the masses – opinion polls do not confirm the radical theses contained in the statements of politicians and journalists.